Inclusión en el aula escolar de comunidad con hipoacusia Revisión documental de publicaciones de 2009 a 2019 - Ladino Peña, Kelly Johana; Cundumí Mancilla, Sara Yisely (Universidad Antonio Nariño, 2021)
It is based on the observation, reading and analysis of 126 documents in which there are undergraduate works, master's doctorates, scientific articles among others to collect various strategies of successful cases such as the use of tics, facial lip technique and language seen from the interdisciplinarity as support and departure for the inclusion of the hearing impaired community in the listening school classroom, becoming in the 3 main categories a cog which cannot exist without the other due to the lack of teacher training regarding sign language as way to supply this shortcoming.